The Effectiveness Of The Absentee Land Ban In Realizing Social Justice For Farmers - Marwiyah Marwiyah; Sri Mulyani; Rudi Mulyanto (Faculty of Law, Universitas Pekalongan, 2025)
Land has a central role in the lives of the Indonesian people, especially in the agricultural sector. However, the practice of land ownership in absentee (guntai) is still a problem that is contrary to the principles of land reform in Indonesia. This study aims to analyze the effectiveness of regulations regarding the prohibition of absentee land ownership and its impact on smallholders. The research method used is normative legal research with a legislative approach and case studies in Banyuwangi Regency. The results of the study show that the ban on absentee land ownership has not been effective due to weak law enforcement, non-compliance with the times, and the practice of buying and selling land under the hands. The conclusion of this study emphasizes the need for stricter land redistribution policies and a transparent land administration system to prevent inequality in land ownership and improve the welfare of smallholders